The moderating role of professional self-efficacy in situations of workplace bullying and self-perceived health - Meseguer de Pedro, Mariano; Soler, María I.; García-Izquierdo, Mariano (Anales de Psicología / Annals of Psychology, 2014)
Self-efficacy is a personal competence stressors acts against increasing or decreasing the psychological discomfort they may generate, meanwhile workplace bullying or mobbing is one of the psychosocial work environment factors more damaging to the health of workers. Using as a framework the theoretical JD-R, this paper’s main objective is to analyze the moderating role of professional self-efficacy between workplace bullying and perceived health status in a multi-occupational sample of 772 workers (379 men and 383 women). An anonymous questionnaire to workers was administered in active-duty after analyzing the data provided by the scale of workplace mobbing NAQ, Questionnaire GHQ-12 for the evaluation of the health and professional self-efficacy of the MBI. The result highlights the moderating role of self-efficacy on health in workplace bullying situations. To these work results of and its possible implication in the organizations are discussed.